Multifrequency full-waveform sonic logging in the screened interval of a large-diameter production well - Almalki, Majed; Harris, Brett; Dupuis, C. (Society of Exploration Geophysics, 2013)
set of field experiments using multiple transmitter center frequencies was completed to test the application potential of low-frequency full-waveform sonic logging in large-diameter production wells. Wireline logs were acquired in a simple open drillhole and a high-yield large diameter production well completed with wire-wound sand screens at an aquifer storage and recovery site in Perth, Western Australia. Phase-shift transform methods were applied to obtain phase-velocity dispersion images for frequencies of up to 4 kHz. A 3D representation of phase-velocity dispersion was developed to assist in the analysis of possible connections between low-frequency wave propagation modes and the distribution of hydraulic properties. For sandstone intervals in the test well, the highest hydraulic conductivity intervals were typically correlated with the lowest phase velocities. The main characteristics of dispersion images obtained from the sand-screened well were highly comparable with those obtained at the same depth level in a nearby simple drillhole open to the formation. The sand-screened well and the open-hole displayed an expected and substantial difference between dispersion in sand- and clay-dominated intervals. It appears that for clay-dominated formations, the rate of change of phase velocity can be associated to clay content. We demonstrated that with appropriate acquisition and processing, multifrequency full-waveform sonic logging applied in existing large-diameter sand-screened wells can produce valuable results. There are few wireline logging technologies that can be applied in this setting. The techniques that we used would be highly suitable for time-lapse applications in high-volume production wells or for reassessing formation properties behind existing historical production wells.Read More: http://library.seg.org/doi/abs/10.1190/geo2012-0328.1